CORRELATIONAND PATH COEFFICIENT ANALYSIS FOR YIELD AND ITS COMPONENTS IN SOYBEAN (GLYCINE MAX L. MERRILL) - SHRUTI KORADDI,; G. T.BASAVARAJA,; SHOBHA IMMADI,; A. G. VIJAYAKUMAR, (The Bioscan, 2015)
The present investigation was carried out in soybean to measure the correlation coefficients and path coefficients using 13 genotypes of soybean. The experiment was laid out in a randomized complete block design with three replications at the Main Agricultural Research Station, University of Agricultural Sciences, Dharwad during kharif 2013.Seed yield per plant (g) was found to have significant and positive correlation with days to 50 flowering (0.3212), plant height (0.3577), number of branches per plant(0.5346), number of pods per plant(0.8486), pod weight per plant(0.9672), 100 seed weight(0.7960), biomass(0.9376) and harvest index(0.8605). While pod length (-0.7421) exhibited significant negative association with seed yield per plant (g). Path coefficient analysis revealed that harvest index had highest positive direct effect (0.5039) on seed yield per plant followed by biomass (0.3382), pod weight per plant (0.2076) and days to 50% flowering (0.1003). The study suggested these characters were considered as most important traits which should be used as selection criteria to develop high yielding varieties in soybean.